Asociación entre características de personalidad y consumo de cigarrillo en adultos de Bucaramanga (Colombia) (2009)
This study intended to see if there is an association between personality traits and daily smoking in adults from Bucaramanga. A transveral population study with a probabilistic sample of adults between 18 and 65 years of age. Personality traits were assesed with the self-report questionnaire of the Structured Clinical Interview for DSM-IV, Axis II (SCID-II), and logistic regression was used in order to control confounding factors. Participants were 2.496 adults, 38 years old on average (SD=13.5); mean schooling was 9.2 years (SD=4.1), 69.7% were women, 58.1% married, 49.1% employed and 67.8% had a middle socioeconomic status. Current smokers (10% of the population) were defined as those who reported daily smoking during the last month. Marked antisocial and borderline traits were found to be independently and modestly associated to current smoking. Nevertheless, it is suggested that personality traits be taken into consideration in prevention programs.